PENGARUH WORKLIFE BALANCE DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) WILAYAH SULUTTENGGO AREA MANADO - Saina, Ischevell Vialara; Pio, Riane Johnly; Rumawas, Wihelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract .This study was conducted to determine the effect of Worklife Balance and Compensation for Employee Performance at PT PLN (Persero) Area Manado.Based on the results of the study states that Worklife Balance employees get a fairly good value, employee satisfaction in achieving harmony between the responsibilities in private life, and the responsibilities of work is urgently needed so that employees can work better, Compensation of employees received value very good, with a proper compensation system can further optimize the performance of employees due to direct impact for employees, Worklife Balance and Compensation together influence Employee Performance by 55.2%, compensation more dominant.It can be concluded that the Worklife Balance and Compensation affects Employee Performance of PT PLN (Persero) Area Manado partially and simultaneously. Recommendations for Human Resource Management is to continue maintaining the system of compensation and attention to the intensity of management policies for employees in order to achieve balancing between work and private life so that Employee Performancewill increasing andCompany goals can be achieved.Keywords: Worklife Balance, Compensation, and Employee Performance.